Olanzapine versus typical neuroleptics for schizophrenia: evaluation of social and economic costs - Mariani, Giorgio; Guidi, Luca; Barioglio, Angelomarco (Farmeconomia. Health economics and therapeutic pathways, 2006)
An important number of publications is reporting results from health outcomes studies comparing atypical antipsychotics (AA) with typical neuroleptics (TN) over 1 year of observation. Our study has prolonged the period observation of the economical and social outcomes to 4 years: 31 patients with schizophrenia were observed retrospectively during two years of TN treatment and then followed during 2 more years of olanzapine treatment after naturalistic switch. The results show a general reduction of health care interventions (territory and hospital) during the olanzapine treatment period. Global costs during olanzapine treatment were lower than during TN treatment (10506 euros with TN vs 6193 euros with olanzapine over 2 years). The social outcome, measured through the registration of the number of working days in the two periods of the study (retrospective with TN and prospective with olanzapine), was better during olanzapine treatment, probably due to increased patient compliance to the rehabilitative activities offered by the Department of Mental Health. In our experience, olanzapine appeared to dominate TN treatment, as its higher acquisition costs were offset by the reduction of territorial and nosocomial health care interventions over two years of observation, and associated with higher involvement in rehabilitative and social activities.